Isolasi dan Identifikasi Senyawa Metabolit Sekunder Ekstrak n-Heksan dari Umbi Lobak (Raphanus Sativus Lamk) - Zahra, Ummi; Muharram, Muharram; Asriani Ilyas, Asriani Ilyas (Al-Kimia, 2013)
Isolation and identification of secondary metabolite compound in extract of n-Hexane in Umbi Lobak (Raphanus sativus Lamk) have been carried out. The purpose of this research is to know secondary metabolite compound which is contained in Umbi Lobak (Raphanus sativus Lamk) which obtained from Gowa. The compound was obtained by isolation process that consists of several steps including extraction, fractination, purification, and identification. Extraction was carried out using maceration with n- hexane. The identification has done by phytochemistry test, melting point, solubility, TLC, and IR spectroscopy. The result of research found out that the obtained compound was the steroid compound, with melt point 133-133,5 oC and had positive reaction toward Lieberman Burchad reagents, where the Lieberman Burchad reagent resulting is green which perfectly solved in n-hexane, bit solved in methanol, and could not be solved in aceton. TLC analysis showed a stain in three scales different solvent and the result of elucidation structure in IR spectrophotometer showed that compound which get is β sitosterol.